2022
DOI: 10.7150/jca.65677
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram Incorporating Preoperative Testing Markers for the prediction of Early Recurrence for Colorectal Liver Metastases with Neoadjuvant Chemotherapy followed by Hepatectomy

Abstract: Background: This study aims to develop a nomogram to predict early recurrence in colorectal liver metastases (CRLM) patients who received neoadjuvant chemotherapy (NAC) followed by hepatectomy. Methods: The primary cohort included 144 CRLM patients treated in the same ward, and 40 CRLM patients from another ward were allocated to the validation cohort. The minimum p value method was used to find the optimal cut-off point for early recurrence. Predictors of early recurrence were determined by univariate analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…In addition, it was reported that the same or different therapies with curative intent after initial treatment for CRLM patients who suffered from early recurrence, such as repeated local treatments ( 25 ), might improve survival outcomes, so the early recognition of these patients would help to guide personalized medical management. Also, the proportion of early recurrence among CRLM patients with recurrence in the current study was consistent with previous studies ( 26 - 28 ). TBS is a prognostic index that combines the impacts of tumour size and number, and many previous studies have explored its utility in discriminating the survival of CRLM patients.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, it was reported that the same or different therapies with curative intent after initial treatment for CRLM patients who suffered from early recurrence, such as repeated local treatments ( 25 ), might improve survival outcomes, so the early recognition of these patients would help to guide personalized medical management. Also, the proportion of early recurrence among CRLM patients with recurrence in the current study was consistent with previous studies ( 26 - 28 ). TBS is a prognostic index that combines the impacts of tumour size and number, and many previous studies have explored its utility in discriminating the survival of CRLM patients.…”
Section: Discussionsupporting
confidence: 92%
“…This review included 24 studies, comprising 12,705 patients who underwent LR for CRLM, with a comprehensive summary presented in Table 1 . Among these, twelve studies adopted a prospective cohort design [ 12 , 18 , 21 , 22 , 28 32 , 34 36 ], with the remaining adopting a retrospective cohort approach [ 14 16 , 19 , 20 , 23 – 27 , 33 , 37 ]. The publication years of the studies spanned from 2007 to 2023.…”
Section: Resultsmentioning
confidence: 99%
“…The publication years of the studies spanned from 2007 to 2023. In terms of geographical distribution, 15 studies originated from Asia [ 14 16 , 19 , 20 , 23 , 24 , 26 , 27 , 29 – 31 , 33 , 35 , 37 ], 7 from Europe [ 12 , 18 , 22 , 25 , 28 , 32 , 34 ], 1 from Australia [ 36 ], and the other one from the United States [ 21 ]. The recruitment period ranged from 1986 to 2020, with the median duration of follow-up ranging varying from 22 to 86.3 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations